HIV-1 CRF07_BC transmission dynamics in China: two decades of national molecular surveillance - Zhangwen Ge; Yi Feng; Hua Zhang; Abdur Rashid; Silvere D. Zaongo; Kang Li; Yueyang Yu; Bowen Lv; Jia Sun; Yanling Liang; Hui Xing; Anders Sönnerborg; et al. (Emerging Microbes and Infections)
By analyzing an unprecedentedly large, longitudinal HIV-1 CRF07_BC sequence dataset collected from China in the past two decades, we sought to build CRF07_BC lengthwise transmission networks, and understand its transmission dynamics. We divided CRF07_BC into two clusters based on phylogenetic analysis and an estimation of the pairwise genetic distance at 0.7%. Of 6213 sequences, 3607 (58.1%) linked to ≥1 other sequence. CRF07_BC was divided into two clusters: 07BC_O and 07BC_N. The 07BC_O is the original CRF07_BC, circulating in people who inject drugs (PWID) and heterosexuals, predominantly in southwestern and northwestern provinces of China. The 07BC_N is a new cluster, identified mostly in men having sex with men (MSM) in the northern provinces of China. Bayesian analysis indicates that CRF07_BC has experienced two phases of exponential growth, which was first driven by 07BC_O then 07BC_N. Compared to 07BC_O, the proportion of the parameter of population transmission risk (TR) of 07BC_N has risen constantly. The power-law function analyses reveal that 07BC_N has increased over years with higher degree. In 07BC_N, only 13.16% of MSM were linked to other risk groups, but these links represent 41.45%, 54.25%, and 55.07% of links among heterosexual females, heterosexual males, and male PWID respectively. This study indicates that CRF07_BC has evolved into two clusters in China, and their distributions are distinct across risk groups and geographical regions. 07BC_N shows a greater risk of transmission, and has gradually replaced 07BC_O. Furthermore, the results show that strengthening the MSM interventions could lower the rapidity of 07BC_N transmission in all risk groups.